Displacement Investigation of KNN-Bitumen-Based Piezoceramics in Asphalt Concrete - Ning Tang; Kaikai Yang; Wenhao Pan; Limei Wu; Qing Wang; Yanwen Chen (Advances in Materials Science and Engineering)
Piezoelectric material has excellent characteristics of electromechanical coupling so that it could be widely applied in structural health monitoring field. Nondestructive testing of piezoelectric technique becomes a research focus on piezoelectric field. Asphalt concrete produces cumulative damage under the multiple repeated vehicle load and natural situation, so it is suited material and structure for nondestructive application. In this study, a test system was established by driving power of piezoceramic, laser displacement sensor, computer, and piezo-embedded asphalt concrete. Displacement, hysteresis, creeps, and dynamic behavior of KNN piezoceramic element embedded in asphalt concrete were tested. The results indicate that displacement output attained 0.4 μm to 0.7 μm when the loads were from 0 N to 150 N. The hysteresis was not obvious when the load was from 0 N to 100 N, aside from higher loads. The creep phenomenon can be divided into two parts: uptrend and balance. The more serious the asphalt binder ageing is, the larger the displacement is, when piezo-asphalt concrete has already been in serious ageing.